PERANCANGAN DESAIN MEBEL SARANA KERJA DAN SIMPAN STUDI KASUS: D’BESTO - Alif, Firman; Hariandini, Tesa Beta (INSIDE : Jurnal Desain Interior, 2024)
The fast food industry in Indonesia, especially D'Besto, faces challenges in creating furniture designs that support operational efficiency and work comfort in their outlets. This study aims to develop functional, efficient and aesthetic work and storage furniture designs according to D'Besto's specific needs. Through direct observation, interviews with users, and a literature review, this research identified several aspects that need improvement, including layout, use of color, product placement, and interactivity. Based on these findings, a new D'Besto booth design was formulated by considering visual design, ergonomics and marketing principles. The research results show that a more attractive, interactive and informative booth design can increase visitor engagement, build brand awareness and ultimately encourage sales conversions. It is hoped that these recommendations will help D'Besto optimize their offline marketing strategy and make a positive contribution to UMKM.